2013
DOI: 10.1126/science.1235771
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Subversion of Host Innate Immune Pathways

Abstract: The pathogenesis of infection is a continuously evolving battle between the human host and the infecting microbe. The past decade has brought a burst of insights into the molecular mechanisms of innate immune responses to bacterial pathogens. In parallel, multiple specific mechanisms by which microorganisms subvert these host responses have been uncovered. This Review highlights recently characterized mechanisms by which bacterial pathogens avoid killing by innate host responses, including autophagy pathways a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 50 publications
5
153
0
Order By: Relevance
“…In plants, the immune response is also mediated by oxidized products of fatty acids, derived from linoleic (18:2 ratio) and linolenic (18:3 ratio) acids in this case (60). Therefore, it is tempting to speculate that Ohr might subvert host immune pathways by some still unknown mechanisms (65). Remarkably, P. aeruginosa contains endogenous enzymatic systems capable of oxidizing unsaturated fatty acids (especially oleic acid) to hydroperoxide and hydroxide derivatives, whose biological function is still elusive (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the immune response is also mediated by oxidized products of fatty acids, derived from linoleic (18:2 ratio) and linolenic (18:3 ratio) acids in this case (60). Therefore, it is tempting to speculate that Ohr might subvert host immune pathways by some still unknown mechanisms (65). Remarkably, P. aeruginosa contains endogenous enzymatic systems capable of oxidizing unsaturated fatty acids (especially oleic acid) to hydroperoxide and hydroxide derivatives, whose biological function is still elusive (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some bacteria produce enzymes that digest mucus to penetrate the protective layer, and many bacteria secrete proteases that can disrupt protective peptides and proteins produced by the host (Baxt et al 2013). Second, the rapid inflammatory responses associated with microbial infections are associated with pattern recognition receptors of the innate immune system, rather than passive defence systems.…”
Section: Innate Immunitymentioning
confidence: 99%
“…6 For instance, adherent invasive Escherichia coli upregulates levels of MIR30C and MIR130A to reduce expression of ATG5 and ATG16L1 and inhibit autophagy. 14 Our study clearly shows that inhibition of autophagy is mediated by directly targeting ATG10 that results in blocking the conversion from MAP1LC3B-I to MAP1LC3B-II, potentially explaining the impaired autophagic clearance of B. pseudomallei.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5] Autophagy, as one of the earliest defense responses encountered by intracellular pathogens, is a process that engulfs and delivers intracellular bacteria for lysosomal degradation. [6][7] However, the battle between the human host and the infecting pathogens is continuously evolving. Preliminary evidence has indicated that several pathogens, such as Shigella, Salmonella, Mycobacteria, and influenza A virus, have evolved mechanisms that evade the autophagic response.…”
Section: Introductionmentioning
confidence: 99%